2004
DOI: 10.1213/01.ane.0000134812.00471.44
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia Before Performing a Spinal Block in the Sitting Position in Patients with Femoral Shaft Fracture: A Comparison Between Femoral Nerve Block and Intravenous Fentanyl

Abstract: We conducted this prospective, randomized study to compare the analgesic effect of femoral nerve block and IV fentanyl administration when given to facilitate the sitting position for spinal anesthesia in patients undergoing surgery for femoral shaft fracture. Five minutes before the placement of spinal block, group FEM patients (n = 10) received a femoral nerve block with lidocaine 1.5% 15 mL, and group IVA patients (n = 10) received IV fentanyl 3 microg/kg. Visual analog scale values during positioning (medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 5 publications
2
71
0
1
Order By: Relevance
“…The time required for performing SAB with FICB was almost half a minute less than that of FNB in the present study. The performance time of FNB arm of our study is comparable to the time reported by Sia et al 10 However, longer SAB performance time of almost seven min has been reported by Yun et al following FICB.…”
Section: Discussionsupporting
confidence: 87%
“…The time required for performing SAB with FICB was almost half a minute less than that of FNB in the present study. The performance time of FNB arm of our study is comparable to the time reported by Sia et al 10 However, longer SAB performance time of almost seven min has been reported by Yun et al following FICB.…”
Section: Discussionsupporting
confidence: 87%
“…Hence the procedure of patient positioning to perform a spinal block, in most cases, requires the administration of IV analgesics. 4 Various modalities like intravenous (IV) fentanyl (FENT), femoral nerve block (FNB) or fascia iliac block with local anaesthetic have been advocated to reduce the pain pre-operatively and improve the positioning of these patients. 4,5 Few studies have demonstrated that a fascia iliac compartment (FIC) block provides effective analgesia for a fractured femur in terms of facilitating an adequate position for spinal anaesthesia or when administered either during pre-hospital management or in emergency departments.…”
mentioning
confidence: 99%
“…4 Various modalities like intravenous (IV) fentanyl (FENT), femoral nerve block (FNB) or fascia iliac block with local anaesthetic have been advocated to reduce the pain pre-operatively and improve the positioning of these patients. 4,5 Few studies have demonstrated that a fascia iliac compartment (FIC) block provides effective analgesia for a fractured femur in terms of facilitating an adequate position for spinal anaesthesia or when administered either during pre-hospital management or in emergency departments. [6][7][8] Systemic analgesics, such as narcotics, are commonly used, but their side effects profile including respiratory depression, cognitive impairment, vomiting, urinary retention, and others limits their clinical utility during injuries of the head, chest, or abdomen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 However due to the pain, analgesics or femoral nerve blockers are given to the patients, before positioning. 8,9 Femoral nerve blockers produce intense anaesthesia with very few side effects compared the opiods and NSAIDS. 10 In addition; the complications with the FNB are rare.…”
Section: Introductionmentioning
confidence: 99%